Multivariable modeling and multivariate analysis for the behavioral sciences - Everitt, Brian S (Boca Raton, Florida CRC Press, 2010)
Multivariable Modeling and Multivariate Analysis for the Behavioral Sciences shows students how to apply statistical methods to behavioral science data in a sensible manner. Assuming some familiarity with introductory statistics, the book analyzes a host of real-world data to provide useful answers to real-life issues.<U+000d><U+000a><U+000d><U+000a>The author begins by exploring the types and design of behavioral studies. He also explains how models are used in the analysis of data.
Data measurement and data -- Looking at data -- Simple linear and locally weighted regression -- Multiple linear regression -- The equivalence of analysis of variance and multiple linear regression and an introduction to the generalized linear model -- Logistic regression -- Survival analysis -- Linear mixed models for longitudinal data -- Multivariance data and multivariate analysis -- Principle components analysis -- Factor analysis -- Cluster analysis -- Grouped multivariate data
Keywords: Análisis multivariante; Ciencias sociales -- Métodos estadísticos